Academic achievement and discipline of children from intact and single-parent families - Tiolengco, Lorna C. (Animo Repository, 1988)
This paper is concerned with the academic achievement and school discipline of children from intact and single-parent (S-P) families. It aims to study whether there are significant relationships between the school performance of selected high school students of Benedictine Abbey School, and Family Type. Furthermore, it aims to find out the significant difference in academic achievement and discipline of students specifically from S-P families. The researcher conducted a purposive sampling of all students from 1st to 3rd year high school. She distributed the Student Data Sheet to all the former 1st, 2nd and 3rd year students, schoolyear 1987-1988, who are presently enrolled at B.A.S. She conducted a room-to-room survey and the returns were classified into the two family type groups. Grade Point Averages (GPA), Average Conduct Grades (ACG), Final Academic Grades, Final Conduct Grades per subject, Number of Academic Failures, Number of Reported Disciplinary cases, were then recorded and the means were computed for each group. To determine if there are significant relationships between school performance and family type, data analysis entailed the use of the Pearson Product Moment Correlation Coefficient, and the t-test. Significant differences in S-P students on the other hand, were tested comparing several sample means, through the use of Analysis of Variance and F-test. For both statistical treatments, the level of significance was tested at .05. Findings show that there is a significant relationship between both Academic Achievement and Discipline and Family Type. Specifically, a relationship was found between GPA/ACG and family type final academic/final conduct grades and family type number of academic failures/number of reported disciplinary cases and family type. In the S-P students, a significant difference in the GPA/ACG of male and female students was found. However, no significant differences were found on GPA/ACG of those whose custodial parent is the father of the mother males and females living with the same or opposite sex parent and those who experienced the disruption before or during adolescence. Therefore, Family Type has a direct implication on students' performance in school. Living with S-P or Intact families has a bearing on students' GPA/ACG, final academic/final conduct grades, number of academic failures and number of reported disciplinary cases. For the S-P students, the males manifest more the effect of marital disruption, with lower academic and discipline performance than females. The effects of mother custodial however, sex of S-P students living with parent of the same sex, and marital disruption before adolescence, does not discriminate the effects of father custodial, sex of S-P students living with parent of the opposite sex, and marital disruption during adolescence. On S-P students' academic achievement and discipline.